STRATEGY FOR DEVELOPMENT OF PANGKAL BABU MANGROVE TOURISM ASOCA METHOD STUDY OF ISLAMIC SUSTAINABLE DEVELOPMENT - Nurida Isnaeni; Nurida Isnaeni; Rafiqi Rafiqi (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study to analyze strategy development Pangkal Babu Mangrove Ecotourism for development sector tour in the village Tungkal I West Tanjung Jabung which became means preservation environment and well-being the surrounding community area in a manner sustainable . As for method analysis used in study is method analysis descriptive use tool ASOCA analysis . The results of this study disclose that strategy development Pangkal Babu Mangrove Ecotourism analyzed in Islamic Sustainable Development studies with increase quality source power human and source power natural with collaboration from various related parties to sustainable optimizing existing opportunities for produce creativity and innovation for ecotourism this own power pull and the quality of tourism that still pays attention to protecting the environment created by Allah SWT and can support the economy of the community around the ecotourism area.